An experimental comparison of mobile texting programs to help young adults quit smoking. Issue 1 (1st March 2017) - Squiers, Linda Brafford; Augustson, Erik; Brown, Derick; Kelly, Bridget; Southwell, Brian; Dever, Jill; Dolina, Suzanne; Tzeng, Janice; Parvanta, Sarah; Holt, Sidney; Sanders, Amy; Zulkiewicz, Brittany; et al.
Abstract: Text messaging interventions may offer promise for health systems, but we need more evidence. We investigated efficacy of three text messaging programs in helping smokers quit. Arm 1 had cessation assessment and quit date reminder messages. Arm 2 had Arm 1 messages plus quit date preparation messages. Arm 3 had Arm 1 and Arm 2 messages plus 6 weeks of post-quit date messaging. Smokers aged 18–29 interested in quitting were randomly assigned to a study arm. We surveyed participants at baseline, and at 3, 8, 20, and 32 weeks ( n  = 4, 027). At 8 weeks, scores on psychological measures were higher in Arm 3 than in Arm 2 or Arm 1. Seven-day smoking abstinence was higher in Arms 3 and 2 than in Arm 1 after controlling for background and psychological measures. Arm 3 affected quitting the most, suggesting motivational text messages before, on, and after an individual's quit date may increase quitting.